2012
DOI: 10.1016/j.seizure.2012.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Markedly disturbed sleep in medically refractory compared to controlled epilepsy – A clinical and polysomnography study

Abstract: Our results indicate that medically refractory epilepsy patients believe that they spend more time sleeping, in contrast to the documented shorter sleep duration on polysomnography. This difference between perceived and actual sleep seems, by their data, to arise mainly from sleep fragmentation, disturbed architecture and the interesting finding of associated sleep apnea among the medically refractory epilepsy patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 11 publications
5
34
1
5
Order By: Relevance
“…40 Many other studies have found high rates of EDS, sleep fragmentation, and disturbed sleep architecture in focal epilepsy, as well as increased risk of obstructive sleep apnea. [41][42][43] Furthermore, several investigations have found that EDS and sleep disturbances are not solely related to antiepileptic medications, [44][45][46] but instead are closely associated with severity and/or duration of disease, [45][46][47] and may be accompanied by decline in quality of life. 44,48 Overall, these clinical studies suggest potential impairment of vigilance networks in focal epilepsy patients.…”
Section: Demonstrating Impaired Vigilance In Epilepsymentioning
confidence: 99%
“…40 Many other studies have found high rates of EDS, sleep fragmentation, and disturbed sleep architecture in focal epilepsy, as well as increased risk of obstructive sleep apnea. [41][42][43] Furthermore, several investigations have found that EDS and sleep disturbances are not solely related to antiepileptic medications, [44][45][46] but instead are closely associated with severity and/or duration of disease, [45][46][47] and may be accompanied by decline in quality of life. 44,48 Overall, these clinical studies suggest potential impairment of vigilance networks in focal epilepsy patients.…”
Section: Demonstrating Impaired Vigilance In Epilepsymentioning
confidence: 99%
“…There is some evidence that patients with epilepsy show a marked disruption in sleep patterns (Zanzmera, et al, 2012), but the few recent studies that have investigated the role of sleep on memory consolidation in patients with epilepsy (e.g., Atherton et al, 2014;Fuentemilla et al, 2013) have yielded somewhat mixed results. The plausible negative effect of nocturnal seizures or epileptiform discharges on sleep patterns and hence memory consolidation has seldom been examined.…”
Section: Autobiographical Experience Memory By 4 Daysmentioning
confidence: 99%
“…A case-control study found among 20 adults with medically refractory epilepsy found that they had less sleep time on overnight polysomnographies (PSGs) (340 vs. 450 min), poorer sleep efficiency (81 vs. 96%), increased wake after sleep onset (20 vs. 4%), and greater number of arousals (10 vs. 5/h) compared with 20 whose epilepsy was well controlled [33]. A study compared the effect of seizures on sleep architecture if a seizure occurred at night or earlier that day in a group of patients with temporal lobe epilepsy (TLE) undergoing prolonged inpatient monitoring with PSG.…”
Section: Objective Effects Of Epilepsy On Sleep Architecturementioning
confidence: 99%